Distribution patterns of pathological venous reflux and risk factors in patients with skin changes due to primary venous disease in North India. (April 2021) - Jain, Prashant; Savlania, Ajay; Behera, Arunanshu; Gorsi, Ujjwal
Objectives: To determine the distribution patterns of pathological venous reflux and risk factors in patients with skin changes due to primary venous disease. Methods: Two hundred limbs belonging to C4, C5 & C6 classes were examined with duplex ultrasound to determine the sites of reflux. We also analyzed the correlation of risk factors with patterns and severity of disease. Results: Among 200 limbs, superficial system reflux was found in 163 limbs (81.5%), deep system reflux in 10 limbs (5%) and perforator system reflux in 180 limbs (90%). The most common pattern of abnormality was combined superficial and perforator system reflux. Of all the risk factors, prolonged standing, obesity and in the female history of pregnancy preceding varicose occurrence had the highest prevalence. Conclusions: In patients with primary chronic venous disease, lifestyle modification is required to avoid risk associated with obesity and prolonged standing. The higher prevalence of pathological perforator reflux in association with advanced venous disease necessitates careful treatment of this least reported pathology to achieve better treatment results.